Efficient preparation of cetyltrimethylammonium bromide-graphene oxide composite and its adsorption of Congo red from aqueous solutions - Su, Jinzhu; He, Shuai; Zhao, Zhigang; Liu, Xingli; Li, Hui (Colloids and surfaces. A, Physicochemical and engineering aspects, 2018)
[Display omitted] •Superior graphene oxide-based adsorbent–CTAB-GO composite was efficiently prepared.•The adsorption process to Congo red was systematically studied.•CTAB-GO composite showed an adsorption capacity as high as 2767 mg/g.•The adsorption capacity was greater than 2000 mg/g even at the tenth cycle. Materials based on graphene oxide (GO) have good adsorption capacities to various water contaminants in recent studies, owing to GO can provide more active sites than reduced graphene oxide. However, the inefficient preparation methods and tedious separation steps after adsorption limit their application in wastewater treatment. In this report, a facile method is proposed for the synthesis of a cetyltrimethylammonium bromide (CTAB)-GO composite via ionic interaction. The hydrophobicity of CTAB-GO composite is enhanced by the alkyl chains of CTAB, and thus, it can be readily separated from water-soluble impurities via low-speed centrifugation (3000 rpm for 3 min). The obtained CTAB-GO composite can efficiently remove the azo dye, Congo red from aqueous solutions, with an adsorption capacity as high as 2767 mg/g. Increasing the initial acidity of the solutions enhances the dye removal process. The adsorption kinetic studies reveal that the adsorption equilibrium achieves in ∼60 min, and the experimental data of the adsorption of Congo red fits well with the pseudo-second-order kinetic model and the Langmuir isotherm. Furthermore, the CTAB-GO composite presents good recyclability and the adsorption capacity is greater than 2000 mg/g even at the tenth cycle.